2010
DOI: 10.1111/j.1939-165x.2009.00182.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased serum acute‐phase protein concentrations with reproductive performance in dairy cows with postpartum metritis

Abstract: Serum Hp and SAA concentrations can be used to recognize uterine infection in postpartum cows. The association between elevated Hp values and number of days open suggests Hp may also be a useful indicator of poor prognosis for reproductive performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
67
4
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(85 citation statements)
references
References 33 publications
(53 reference statements)
6
67
4
6
Order By: Relevance
“…Similarly, Ametaj (2005) and Tothova et al (2008) reported an increase of the two main acute phase proteins, Hp and SAA, in cows after parturition. According to the results presented by Chan et al (2010), the SAA concentrations in healthy cows reach their highest values within three days after the delivery.…”
Section: Acute Phase Proteins In Reproduction and Peripartum Reproducmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ametaj (2005) and Tothova et al (2008) reported an increase of the two main acute phase proteins, Hp and SAA, in cows after parturition. According to the results presented by Chan et al (2010), the SAA concentrations in healthy cows reach their highest values within three days after the delivery.…”
Section: Acute Phase Proteins In Reproduction and Peripartum Reproducmentioning
confidence: 99%
“…Chan et al (2004) evaluated clinically healthy cows and cows with post partum reproductive diseases after calving, and observed that Hp concentrations in clinically diseased cows were significantly higher than in clinically healthy cows. In a later study of Chan et al (2010), cows with acute puerperal metritis had significantly higher Hp concentrations than healthy cows. The highest Hp concentration was found in the period of three days after parturition, and for SAA concentrations four to seven days post partum.…”
Section: Acute Phase Proteins In Reproduction and Peripartum Reproducmentioning
confidence: 99%
“…Many studies have indicated the significance of Hp and SAA as a clinically useful parameter for measuring the occurrence and severity of inflammatory responses in cattle with endometritis (Ceron et al 2012;Chan et al 2010;Sahoo & Mohanty 2014). In the present study, serum Hp and SAA levels in endometritic cows were found to be higher than reference values of healthy cows.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, serum Hp and SAA levels in endometritic cows were found to be higher than reference values of healthy cows. Serum APPs have been proposed as predictors of uterine infection (Huzzey et al 2009;Chan et al 2010;Dubuc et al 2010). …”
Section: Discussionmentioning
confidence: 99%
“…Veterinary Biomarker Discovery: Proteomic Analysis of Acute Phase Proteins 191 2.1 Modulation of acute phase proteins during disease in swine Alteration in APP expression has been associated with a number of food animal diseases (Table 1), including mastitis, metritis, and amyloidosis in lactating dairy cattle (Chan et al, 2010;Safi et al, 2009;Suojala et al, 2008;Eckersall et al, 2001Eckersall et al, , 2006Takahashi et al, 2006;Grönlund et al, 2003Grönlund et al, , 2005; sepsis, trauma, and respiratory diseases in swine (Amory et al, 2007;Sorensen et al, 2006;Hultén et al, 2003;Heegaard et al, 1998;Eckersall et al, 1996); infectious bronchitis virus in chickens (Nazifi et al, 2011); respiratory diseases in beef cattle (Orro et al, 2011;Heegaard et al, 2000;Godson et al, 1996;Horadagoda et al, 1995); as well as pulmonary damage and caseous lymphadenitis in sheep (Eckersall et al, 2007;Pfeffer and Rogers, 1989 In swine, increased levels of serum HPT have been associated with pathological indications of Mycoplasma hyopneumoniae, a leading cause of porcine enzootic pneumonia (Amory et al, 2007). Similarly, serum concentrations of HPT and SAA were elevated in pigs with experimentally induced Actinobacillus pleuropneumoniae pneumonia Heegaard et al, 1998).…”
Section: Wwwintechopencommentioning
confidence: 99%